(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Acetic acid (Acidum aceticum) CH3–COOH has been known as "vinegar" since ancient times, its composition was discovered by the Swedish chemist Berselius in 1814. From Wikipedia